Acupuncture versus placebo acupuncture for in vitro fertilisation: a systematic review and meta-analysis. Issue 1 (February 2021) - Coyle, Meaghan E; Stupans, Ieva; Abdel-Nour, Katherine; Ali, Hiba; Kotlyarsky, Michelle; Lie, Phillip; Tekin, Sinan; Thrimawithana, Thilini
Objective: To evaluate the efficacy of acupuncture compared to placebo acupuncture for women undergoing in vitro fertilisation (IVF) in a systematic review and meta-analysis. Methods: A search was conducted in seven English-language biomedical databases from their inception to 3 April 2019 to identify studies evaluating acupuncture as an adjunct to IVF treatment. Randomised controlled trials (RCTs) that compared acupuncture with placebo acupuncture using a non-invasive placebo acupuncture device in women undergoing a fresh or frozen IVF cycle were eligible, as were studies that tested placebo acupuncture as the intervention. Outcomes were clinical pregnancy rate, ongoing pregnancy rate, miscarriage rate, live birth rate and adverse events. Results: Eight RCTs involving 3607 women were included. Studies were judged to be low risk for most of the risk of bias domains. Acupuncture around the time of embryo transfer was not significantly different to placebo acupuncture in terms of the clinical pregnancy rate (6 RCTs, 2473 women, risk ratio (RR) = 0.99 (95% confidence interval (CI) = 0.88, 1.11), I 2  = 51%, moderate certainty evidence), ongoing pregnancy rate (4 RCTs, 1459 women, RR = 0.88 (95% CI = 0.75, 1.02), I 2  = 50%, moderate certainty evidence), miscarriage rate (4 RCTs, 502 women, RR = 1.23 (95% CI = 0.89, 1.71), I 2  = 30%, high certainty evidence) or live birth rate (4 RCTs, 1835 women, RR = 0.87 (95% CI = 0.75, 1.01), I 2  = 0%, high certainty evidence). Outcomes with placebo acupuncture were not significantly different to usual care. Adverse events relating to acupuncture, such as discomfort and bruising, were mild to moderate. Conclusion: Acupuncture administered around the time of embryo transfer did not have a statistically significant effect on IVF outcomes compared with placebo acupuncture.